Magic in Old Norse-Icelandic literature: a typology of modes - Stephen A. Mitchell (Filologia Germanica, 2025)
Magic often plays a significant role in medieval European narratives, where it can be used in a variety of ways, including as a literary tool. In this essay, I briefly consider magic as a narrative device and propose a typology of modes of presentation (general, detailed, and explicit), and argue that Old Norse-Icelandic literature appears to engage in an especially wide array of narrative presentations of magic, particularly when contrasted with comparable materials from elsewhere in northern Europe.